Letter: different risks of venous thromboembolism in subsets of patients with inflammatory bowel diseases – authors' reply. Issue 3 (20th January 2019) - Chu, Thomas P. C.; Grainge, Matthew J.; Card, Timothy R.
Abstract : Linked Content This article is linked to Chu et al and Ding et al papers. To view these articles, visit https://doi.org/10.1111/apt.15010 and https://doi.org/10.1111/apt.15083 .